CCAAT/Enhancer-Binding Protein Alpha Is a Novel Regulator of Vascular Smooth Muscle Cell Osteochondrogenic Transition and Vascular Calcification - Chen, Pengyuan; Hong, Wanzi; Chen, Ziying; Gordillo-Martinez, Flora; Wang, Siying; Fan, Hualin; Liu, Yuanhui; Dai, Yining; Wang, Bo; Jiang, Lei; Yu, Hongjiao; He, PengCheng (Frontiers in Physiology, 2022)
Aims: Vascular calcification is a common clinical complication of chronic kidney disease, atherosclerosis and diabetes, which is associated with increased cardiovascular morbidity and mortality in the patients. The transdifferentiation of vascular smooth muscle cell (VSMC) to an osteochondrogenic phenotype is a crucial step during vascular calcification. The transcription factor CCAAT/enhancer-binding protein alpha (C/EBPα) plays an important role in regulating cell proliferation and differentiation, but it remains unclear whether C/EBPα regulates calcification of arteries and VSMCs. This study aims to understand the role of C/EBPα in the regulation of vascular calcification Methods and Results: Both mRNA and protein expression levels of C/EBPα were significantly increased in calcified arteries from mice treated with a high dose of vitamin D3 (vD3). The up-regulation of C/EBPα was also observed in the high phosphate and calcium-induced VSMC calcification process. siRNA-mediated knockdown of C/EBPα significantly attenuated VSMC calcification in vitro. Moreover, depletion of C/EBPαin VSMCs significantly reduced mRNA expression of the osteochondrogenic genes including Bmp2 and Sox9. Comparable changes in protein expression of Sox9 was also observed in VSMCs depleted of C/EBPα, while no difference of BMP2 expression was observed. Additionally, silencing of Sox9 expression significantly inhibited high phosphate and calcium-induced VSMC calcification in vitro. Conclusion: These findings indicate that C/EBPα is a key regulator of VSMC osteochondrogenic transdifferentiationand vascular calcification, and may represent a novel therapeutic target for vascular calcification.